Fabrication of environmental humidity-responsive iridescent films with cellulose nanocrystal/polyols. (15th July 2020) - Meng, Yahui; Cao, Yunfeng; Ji, Hairui; Chen, Jie; He, Zhibin; Long, Zhu; Dong, Cuihua
Highlights: Polyol as the plasticizer significantly improved the flexibility of iridescent CNC film. Polyol efficiently tuned the pitch size of the chiral nematic structure in iridescent CNC film. CNC-S film exhibited a large colour-change range, good reversibility, and excellent stability. CNC-S film was highly sensitive to environmental humidity changes. Abstract: Herein, we fabricated flexible and humidity-sensitive composite films employing cellulose nanocrystal (CNC) and polyols, i.e., glycerol (G), xylitol (X) and sorbitol (S). The effects of polyols with different molecular weights on the structure, optical properties, mechanical strength and humidity response of the composite films were investigated. Notably, the CNC-S film exhibited obvious reversible colour changes from light green to red upon a relative humidity (RH) change from 30 % to 95 %. Moreover, it was found that the composite films had a large colour-change range, good reversibility (>10 cycles), and excellent stability (>10 weeks). Overall, the results demonstrated that the CNC-S composite film can be used as a functional material for the preparation of flexible humidity sensors for the detection of environmental humidity changes in agriculture, industry, and other fields.